Retrieval of broken balloon from left anterior descending artery during percutaneous coronary intervention - Bhardwaj Saurabh; Sharma Ruchi; Gupta LC; Yadav Uday Singh; Vinod Sharma (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
A 64-year-old male patient presented to the Emergency Room (ER) of our hospital with complaints of precordial pain associated with profuse sweating for the past 8 hours.